Entrepreneurial Strategies, Entrepreneur’s Typology and Enterprise Performance in Ghana - Antoh, N.A.D. (University of Ghana, 2023)
The purpose of this research is to examine the relationship that exists between entrepreneurial strategy and firm performance by using entrepreneur types as a moderator. The study considered the entrepreneurial strategy; as effectuation, causation, and bricolage and how they affect enterprise performance while considering the type of entrepreneurs; necessity or opportunity in enterprise operation as a moderator (An, Rüling, Zheng & Zhang, 2020). This research study embraces the quantitative approach due to the variables under study and the attempt to examine the relationship among them. The population for this study is small-scale entrepreneurs operating in Ghana. After identifying a study population, data was collected using a random probability sampling procedure, the study collects data from two hundred and eighteen (218) respondents. From the findings, it was evident that, entrepreneurial both entrepreneurial strategies and entrepreneurial typologies are essential to enterprise performance. Essentially, the study reveals interestingly that opportunity entrepreneurs are better off utilizing causation strategies whereas necessity entrepreneurs will thrive on effectuation and bricolage strategies. This study makes significant contribution to literature in entrepreneurship opportunities, entrepreneurial strategies and enterprise performance in an emerging economy like Ghana. The study finally recommends that future researchers consider a qualitative research approach to further ascertain the findings of this study.
MPhil. Marketing
Keywords: entrepreneurial strategy; firm performance; Ghana